Overcoming hypoxia-induced breast cancer drug resistance: a novel strategy using hollow gold-platinum bimetallic nanoshells - Lian-Ying Zhang; Xiao-Tong Chen; Rong-Tian Li; Wei Meng; Guo-Qin Huang; Yong-Jian Chen; Feng-Jun Ge; Qun Zhang; Yu-Jun Quan; Cai-Tao Zhang; Yi-Fei Liu; Ming Chen; et al. (Journal of Nanobiotechnology)
Abstract Breast cancer (BC) is a significant cause of cancer-related deaths among women worldwide. Hypoxia, a common feature of solid tumor, is associated with drug resistance and a poor prognosis in BC. In this study, we present a strategy to overcome hypoxia-induced chemotherapy tolerance in BC. Specifically, we synthesized a hollow gold (Au)-platinum (Pt) bimetallic nanoshell for the first time, which acted as a drug delivery system (DDS) for doxorubicin (DOX). The photothermal effect, induced by the surface plasmon resonance (SPR) from the Au-Pt shell under near infrared-II (NIR-II) laser irradiation, not only directly causes tumor cell death through photothermal therapy (PTT), but also significantly enhances the catalase-like activity between Pt nanoparticles and endogenous H2O2. This, subsequently, results in a heightened yield of O2, which further facilitates the release of DOX. This process alleviates tumor hypoxia and down-regulating hypoxia-inducible factor-1α (HIF-1α), multidrug resistance gene 1 (MDR1), and P-glycoprotein (P-gp), which can reverse drug resistance and achieve more effective DOX chemotherapy effects. Significantly, the increased availability of oxygen further re-polarizes immunosuppressive M2 macrophages into antitumor M1 macrophages. This study presents a novel strategy to tackle tumor proliferation and enhance tumor response to chemotherapy, offering hope for reversing in drug resistance in cancerous lesions. Graphical Abstract